2021
DOI: 10.4240/wjgs.v13.i11.1351
|View full text |Cite
|
Sign up to set email alerts
|

Is surgery the best treatment for elderly gastric cancer patients?

Abstract: As the elderly population increases, the number of patients with gastric cancer has also been increasing. Elderly people have various preoperative problems such as malnutrition, high frequency of comorbidities, decreased performance status, and dementia. Furthermore, when surgery is performed, high postoperative complication rates and death from other diseases are also concerns. The goal of surgery in the elderly is that short-term outcomes are comparable to those in nonelderly, and long-term outcomes reach li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 79 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…Elderly patients have an increased risk of surgical complications due to underlying diseases, decreased physical performance and malnutrition. Therefore, choosing a reasonable surgical strategy is very important[ 18 ]. Previous results have shown that the incidence of postoperative complications in elderly patients undergoing LG is comparable with that in younger patients, confirming that laparoscopic surgery is a safe method for elderly patients with GC[ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients have an increased risk of surgical complications due to underlying diseases, decreased physical performance and malnutrition. Therefore, choosing a reasonable surgical strategy is very important[ 18 ]. Previous results have shown that the incidence of postoperative complications in elderly patients undergoing LG is comparable with that in younger patients, confirming that laparoscopic surgery is a safe method for elderly patients with GC[ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with gastric cancer, the use of laparoscopic gastrectomy has become widespread as a minimally invasive procedure and with reduction in postoperative complications [8]. We are probably not there yet where a fully ambulatory procedure for gastric cancer can be implemented but the emerging widespread use of laparoscopic surgery for this disease may be the first step in that direction.…”
Section: Minimally Invasive Surgery and Improvement Of Surgical Techn...mentioning
confidence: 99%
“…While surgery remains the primary treatment, the advanced age of these patients often corresponds with increased surgical risks and comorbidities, necessitating a nuanced treatment approach. It is critical to balance the potential benefits of surgery against the risks of postoperative complications in this demographic [ 4 8 ]. Effective management of these complications is essential not only to improve immediate surgical outcomes but also to reduce non-cancer mortality, further underscoring the importance of postoperative care [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous study demonstrated that perioperative geriatric care significantly reduces hospital stays and ICU usage in these patients [ 10 ], underscoring the value of comprehensive preoperative assessments. This approach is crucial in addressing the diverse medical needs of this population and ensuring favorable surgical outcomes [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%